Lokamānya Tiḷaka yāñcyā āṭhavaṇī va ākhyāyikā - Bāpaṭa, Sadāśiva Vināyaka, b. 1887 (Sadāśiva Vināyaka Bāpaṭa, 1924)
Collection of writings on Bal Gangadhar Tilak, 1856-1920, Indian freedom fighter, by his friends and associates.